Path planning of linear trajectories on an experimental delta pick and place manipulator (2016)
This paper aims to study the motion of an experimental prototype of a Delta robot funded by Universidad Santo Tomas according to the second internal call of hotbed of research 2010-2011 with the project code 2010115. To continue with the research of MAIR (Mechanical Association for Indus- trial Research), and bring the project to possibly industrial applications, it is necessary to characterize the appropriate drivers for the experimental Delta robot motions, for being able to implement a movement of a trajec- tory in space. All the trajectories will be supported by inverse kinematics equations for a 3 DOF (Degrees Of Freedom) parallel architecture robot, to identify the position of the end e ector from one coordinate in space to another. In long terms, it is intended to provide detailed information of trajectories in the space that will make easier the process of motion control with educational controllers or industrial controllers, as this would come to be a new project.